2006
DOI: 10.1016/j.aquaculture.2006.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution in a temperate coastal ecosystem of the wild stock of the farmed oyster Crassostrea gigas (Thunberg)

Abstract: The Pacific oyster, Crassostrea gigas, well known throughout the world because of its ability to adapt to a wide range of environmental conditions, was introduced for cultivation into France on a massive scale in the 1970s. With global warming, the reproductive population, confined at the beginning to the south of the French Atlantic coast, became established at more northern latitudes (above 45° 58′ N), and wild C. gigas began to colonize coastal areas such as our study site, Bourgneuf Bay (1°-2° W, 46°-47° N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 16 publications
2
38
0
7
Order By: Relevance
“…Climate-driven ocean warming, however, may lead to a more detrimental impact of C. gigas on species diversity by establishing high density populations, thus reducing associated species diversity (Cognie et al, 2006;Syvret et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Climate-driven ocean warming, however, may lead to a more detrimental impact of C. gigas on species diversity by establishing high density populations, thus reducing associated species diversity (Cognie et al, 2006;Syvret et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…During recent decades, C. gigas benefited from coastal eutrophication and rising sea temperature (Thomas et al, 2016), resulting in a poleward expansion of its distribution (Dutertre et al, 2010) and the formation of dense reefs along many coastal areas (Diederich, 2006;Brandt et al, 2008;Le Bris et al, 2016). In some ecosystems, wild C. gigas is now considered as a trophic competitor of its cultivated conspecifics (Cognie et al, 2006). Newly established oyster populations also impact biogeochemical fluxes and ecosystem processes, 906 C. Echappé et al: RS reveals oyster reefs' positive impact on MPB development leading to both positive (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, rocky western coasts of France (including the Bay of Brest) have been heavily colonized by wild oysters Crassostrea gigas in the last decade (Cognie et al 2006). Lejart & Hily (2011) investigated the consequences for the Bay of Brest and reported that mass biodeposits from the invasive oyster reefs were washed away from the reefs and sedimented in deeper areas of the bay.…”
Section: Ophiuroid Success Linked With Human-induced Environmental Chmentioning
confidence: 99%